2006
DOI: 10.1074/jbc.m605905200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways Regulating Pro-migratory Effects of Hedgehog Signaling

Abstract: The Hedgehog proteins play a crucial role in metazoan embryo development. Constitutive activation of the pathway is associated with multiple types of cancer. Recent experimental data suggest involvement of Hedgehog signaling in vascular remodeling, germ cell migration, and axon guidance. The molecular mechanisms underlying these effects remain elusive. Here we show that yolk sac-derived endothelial cells and embryonic fibroblasts can directly respond to the Hedgehog signal by increased migration in an in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 53 publications
3
50
0
Order By: Relevance
“…Studies conducted by Hochman and colleagues have suggested that the components of the Shh signaling pathway participate directly in cell migration and angiogenesis, whereas inhibition of this pathway blocks Shhinduced cell migration and angiogenesis (4). In addition, Shh and Gli1 expression has also been shown to affect epithelial-tomesenchymal transition (EMT) in pancreatic cancer cell lines and lymphatic metastasis in esophageal squamous cell carcinoma (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted by Hochman and colleagues have suggested that the components of the Shh signaling pathway participate directly in cell migration and angiogenesis, whereas inhibition of this pathway blocks Shhinduced cell migration and angiogenesis (4). In addition, Shh and Gli1 expression has also been shown to affect epithelial-tomesenchymal transition (EMT) in pancreatic cancer cell lines and lymphatic metastasis in esophageal squamous cell carcinoma (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been confirmed that the Hh pathway participates in cell migration and angiogenesis processes and is correlated with the severity of the associated tumor (27)(28)(29), additionally, disruption of Hh pathway has been shown to inhibit metastasis in pancreatic cancer and gastric cancer (29)(30)(31), the relationship between the Hh signaling pathway and aggressiveness of HCC cells remains unclear. It is necessary to investigate whether the signaling influences proliferative and invasive potential of HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…SHH CM was prepared as described previously (Ingram et al 2002, Hochman et al 2006, Park et al 2011. Briefly, media were collected from SHHN-923 cells, which were transfected to secrete active SHH (N-terminal domain) in a pMT21 (pSHH-N-PMT21) plasmid.…”
Section: Shh Studymentioning
confidence: 99%